If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(156x + -13) = 0 Reorder the terms: -1(-13 + 156x) = 0 (-13 * -1 + 156x * -1) = 0 (13 + -156x) = 0 Solving 13 + -156x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -156x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -156x = 0 + -13 -156x = 0 + -13 Combine like terms: 0 + -13 = -13 -156x = -13 Divide each side by '-156'. x = 0.08333333333 Simplifying x = 0.08333333333
| hg(x)=3.08(x)sqrt+18.97 | | 232=4(8n-6) | | 100=4(4-3x) | | -(156-13)= | | 95=5(4-3n) | | 2.28x-.8=2x+1.8 | | Hg(x)=3.08(52)sqrt+18.97 | | -5(-1-2p)+5p=95 | | .8x+.2=.6x+-10 | | 3x-7-x=5x+14 | | 6y-10=2+4y | | 5x-11=4x+7 | | -217=-6(-6v-6)-1 | | 6(7+3x)=150 | | 0=-5n-2m | | 18x+21=10x+90 | | -317=3+5(8k-8) | | 9y-3=4+2y | | X=3xj-4 | | 4x+7(1-5x)=-210 | | (-9,2)(-10,-4)= | | 4x^2+4x+9=0 | | 7m=5+8m | | 9t-14=-26+5t | | 3(k+2)=21 | | x^2-kx+3=0 | | x-0.8=8.29 | | 2u^2-3u+1=0 | | (2x-5)(3x-2)= | | 20z=100 | | 9x+10x=21 | | 4(x+7)=52 |